Hydrocephalus Shunting in Supratentorial Glioblastoma: Functional Outcomes and Management - El Rahal, Amir; Cipriani, Debora; Fung, Christian; Hohenhaus, Marc; Sveikata, Lukas; Straehle, Jakob; Shah, Mukesch Johannes; Heiland, Henrik Dieter; Beck, Jürgen; Schnell, Oliver (Frontiers in Oncology, 2022)
Background Glioblastoma is the most common and the most challenging to treat adult primary central nervous system tumor. Although modern management strategies modestly improved the overall survival, the prognosis remains dismal associated with poor life quality and the clinical course often dotted by treatment side effects and cognitive decline. Functional deterioration might be caused by obstructive or communicating hydrocephalus but due to poor overall prognosis surgical treatment options are often limited and its optimal management strategies remain elusive. We aimed to investigate risk factors, treatment options and outcomes for tumor-associated hydrocephalus in a contemporary 10 years cohort of glioblastoma patients. Methods We reviewed electronic health records of 1800 glioblastoma patients operated at the Department of Neurosurgery, Medical Center – University of Freiburg from 2009 to 2019. Demographics, clinical characteristics and radiological features were analyzed. Univariate analysis for nominal variables was performed either by Fisher’s exact test or Chi-square test, as appropriate. Results We identified 39 glioblastoma patients with symptomatic communicating hydrocephalus treated by ventricular shunting (incidence 2.1%). Opening of the ventricular system during a previous tumor resection was associated with symptomatic hydrocephalus (p<0.05). There was also a trend toward location (frontal and temporal) and larger tumor volume. Number of craniotomies before shunting was not considered as a risk factor. Shunting improved hydrocephalus symptoms in 95% of the patients and Karnofsky Performance Score (KPS) could be restored after shunting. Of note, 75% of the patients had a post-shunting oncological treatment such as radiotherapy or chemotherapy, most prevalently chemotherapy. Infection (7.7%) and over- or under drainage (17.9%) were the most common complications requiring shunt revision in ten patients (25.6%), No peritoneal metastasis was found. The median overall survival (OS) was 385 days and the median post shunting survival was 135 days. Conclusion Ventricular system opening was identified as a risk factor for communicating hydrocephalus in glioblastoma patients. Although glioblastoma treatment remains challenging, shunting improved hydrocephalus-related functional status and may be considered even in a palliative setting for symptom relief.